Immunohistological demonstration of progesterone receptor in breast carcinomas: correlation with radioligand binding assays and oestrogen receptor immunohistology. Issue 4 (April 1988) - Giri, D D; Goepel, J R; Rogers, K; Underwood, J C
Abstract : The validity of determining the progesterone receptor status of breast carcinomas with a monoclonal antibody was investigated by comparison with data from a radioligand binding assay on adjacent cryostat sections of 103 tumours. Significant nuclear staining for progesterone receptor was observed in 37 (36%) of the tumours studied and this showed a close correlation with the results of radioligand binding assays for progesterone receptor. In three progesterone receptor positive tumours there was an apparent paradoxical absence of oestrogen receptor; progesterone receptor normally depends on the presence of oestrogen receptor, but these rare tumours may be essentially progesterone receptor positive. It is concluded that this monoclonal antibody is an appropriate reagent for use in the immunohistological determination of progesterone receptor status of breast carcinomas; that it advantageously identifies both the occupied and unoccupied receptor sites; and that it provides information about tumour cell heterogeneity with respect to receptor status.